Connecting the World: The Utilization of ICT for Rural Teacher Education in Indonesia - Aziz Awaludin (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract This study aims to explore the impacts of the convergence of ICT (information and communication technology) for training in-service elementary school teachers in Indonesia. As a country in which almost a half of its population live in rural areas, Indonesia has a very serious issue with the quality divide which is quite extensive between urban and rural teachers. Thus, the use of ICT can be an alternative to reduce the gap, facilitate social justice and, therefore, connect the rural teachers to the world. Particularly, this study is focused on benefits and constraints of the issue when applied in that rural setting. The investigation is based on a literature review that certain academic refereed journal articles are analysed. Then, the analysis shows that infusing ICT can impact positively in the way that its advantages involve the expansion of opportunities for rural teachers to receive continuous training, collaborative actions among teachers from different schools, skills and resource development to upgrade their competencies. However, the implementation invites several limitations linked to financial, technical, geographical, and personnel-related issues. Also, the study points out several implications regarding policy and research areas. Then, some recommendations are offered to tackle the possible challenges that may occur. Abstrak Penelitian ini bertujuan untuk menggali dampak konvergensi TIK (teknologi informasi dan komunikasi) untuk pelatihan calon guru sekolah dasar di Indonesia. Sebagai negara di mana hampir separuh penduduknya tinggal di daerah pedesaan, Indonesia memiliki masalah yang sangat serius dengan perbedaan kualitas yang cukup luas antara guru perkotaan dan pedesaan. Dengan demikian, penggunaan TIK dapat menjadi alternatif untuk mengurangi kesenjangan, memfasilitasi keadilan sosial dan, oleh karena itu, menghubungkan para guru pedesaan ke seluruh dunia. Secara khusus, penelitian ini difokuskan pada manfaat dan kendala masalah saat diterapkan di lingkungan pedesaan tersebut. Penyelidikan didasarkan pada tinjauan literatur di mana beberapa artikel jurnal akademik dianalisis. Kemudian, analisis menunjukkan bahwa menanamkan TIK dapat berdampak positif dengan cara bahwa kelebihannya melibatkan perluasan kesempatan bagi guru pedesaan untuk menerima pelatihan berkelanjutan, tindakan kolaboratif di antara guru dari berbagai sekolah, keterampilan dan pengembangan sumber daya untuk meningkatkan kompetensi mereka. Namun, implementasinya mengundang beberapa keterbatasan terkait masalah keuangan, teknis, geografis, dan personil. Selain itu, penelitian tersebut menunjukkan beberapa implikasi mengenai area kebijakan dan penelitian. Kemudian, beberapa rekomendasi ditawarkan untuk mengatasi kemungkinan tantangan yang mungkin terjadi. How to Cite : Awaludin, A. (2016). Connecting the World: The Utilization of ICT for Rural Teacher Education in Indonesia. TARBIYA: Journal of Education in Muslim Society, 3(2), 218-226. doi:10.15408/tjems.v3i2.4984. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.4984